Biological therapies for psoriasis. (December 2013) - Mansouri, Bobbak; Patel, Mahir; Menter, Alan
Abstract : Introduction: Biological therapies have revolutionized moderate-to-severe psoriasis treatment. Increased understanding of disease pathogenesis has yielded multiple therapeutic targets involving the IL-23/Th17 pathway, while current therapies continue to be monitored for long-term efficacy and safety. Areas covered: This review details current understanding of psoriasis immunopathogenesis specifically related to therapeutic targets. Approved and emerging biological psoriasis therapies targeting TNF-α, IL-12/23p40, IL-17 and IL-23p19 are covered. Biological agent uses in special circumstances are reviewed together with the emerging debate on biosimilar therapies and their potential future role in psoriasis and other inflammatory diseases. Expert opinion: Psoriasis treatment has expanded and has become more effective due to increased understanding of disease pathogenesis. However, lack of efficacy in select psoriasis patients, safety concerns and limited treatment efficacy in psoriasis variants (e.g., pustular) are areas which still need improvement. As such, pharmacogenomics will be of vital importance in future for individualized psoriasis care. Further, a better understanding of the multiple psoriasis comorbidities, especially cardiovascular disease, continues to be of significant interest in the psoriasis community. Last, the emergence of biosimilar agents has the potential to change psoriasis treatment, especially as it relates to better access for the psoriasis community worldwide.